2020
DOI: 10.11591/ijere.v9i4.20877
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of parental attitude and preferences towards implementation of sexuality education

Abstract: Parents play a unique role in providing and facilitating their children in acquirement of sexual and reproductive health knowledge. The purpose of this study is to provide an overview of parents’ attitude, preferences towards sexuality education (SE) and factors that contributed to their attitudes and perceptions based on review of relevant literature. The articles were retrieved via electronic databases, and manually examined to identify the studies that addressed the research questions. There were 29 studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…They also stated that SE should be age-appropriate and tailored to the individual’s mental development, and education should be at a level that is understandable by children, similar to previous studies [ 38 , 45 , 46 ]. To meet parents’ perceived requirements and unmet needs of children with ID, Sravanti and Jayendra offered a model that described the “What, Why, and How” of five constructs to ease in providing SE: understanding human body, hygiene and self-care, social skills, privacy, safety, and handling feelings [ 46 ].…”
Section: Discussionmentioning
confidence: 62%
“…They also stated that SE should be age-appropriate and tailored to the individual’s mental development, and education should be at a level that is understandable by children, similar to previous studies [ 38 , 45 , 46 ]. To meet parents’ perceived requirements and unmet needs of children with ID, Sravanti and Jayendra offered a model that described the “What, Why, and How” of five constructs to ease in providing SE: understanding human body, hygiene and self-care, social skills, privacy, safety, and handling feelings [ 46 ].…”
Section: Discussionmentioning
confidence: 62%
“…A cross-sectional study carried out among the parents of Nigeria to determine the perception of timing and initiation of sexuality discussion with adolescents indicated that most parents preferred to initiate sexuality discussion with children only after puberty (14). Moreover, a systematic review that was carried out to assess parents' preference for sexuality education of adolescents, pointed out that parents perception of their children as too young to receive SRH information is a barrier to discussing sexual health matters with children (15).…”
Section: Discussionmentioning
confidence: 99%
“…However, the review of literature from western cultures indicated that mothers were okay with initiating sexual education for their children at a younger age like elementary school or before (15). A similar study carried out in the west found that the pre-adolescent age from 11-14 years is the best time for mothers to start sexuality discussions with their children since the children are more inquisitive during this phase and undergoing physical and psychological discomfort (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when developing these measurements, most researchers were targeting on parents of high school students (Odebode, 2019; Peter et al, 2015; Welshimer & Harris, 1994) with limited evaluation tools for parents with children attending primary schools. Parents’ expectations for sexuality education could be varied based on physical and mental maturity of their children (Barr et al, 2014; Yeo & Lee, 2020). Parents with older children might think sexuality education is more relevant to their children’s need.…”
Section: Literature Reviewmentioning
confidence: 99%